CREATING COMPUTER PROGRAMS USING SPECIFIC PROGRAMMING LANGUAGES - Toshpulatov Rakhimjon Ismailovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article devoted to imrove the process and art of creating computer programs using specific programming languages. It is also stated that a particular programming language is based on some guiding idea that significantly influences the style of the corresponding programs.